Combination therapy in type 2 diabetes mellitus: adding empagliflozin to basal insulin - Andrew Ahmann (BioExcel Publishing Ltd, 2015)
Type 2 diabetes mellitus (T2DM) management is complex, with few patients successfully achieving recommended glycemic targets with monotherapy, most progressing to combination therapy, and many eventually requiring insulin. Sodium glucose cotransporter 2 (SGLT2) inhibitors are an emerging class of antidiabetes agents with an insulin-independent mechanism of action, making them suitable for use in combination with any other class of antidiabetes agents, including insulin. This review evaluates a 78-week, randomized, double-blind, placebo-controlled trial investigating the impact of empagliflozin, an SGLT2 inhibitor, as add-on to basal insulin in patients with inadequate glycemic control on basal insulin, with or without metformin and/or a sulfonylurea. Empagliflozin added on to basal insulin resulted in significant and sustained reductions in glycated hemoglobin (HbA1c) levels compared with placebo. Empagliflozin has previously been shown to induce weight loss, and was associated with sustained weight loss in this study. This combination therapy was well tolerated, with similar levels of hypoglycemic adverse events in the empagliflozin and placebo groups over the 78-week treatment period. Urinary tract infections and genital infections, side effects associated with SGLT2 inhibitors, were reported more commonly in the empagliflozin group; however, such events led to treatment discontinuation in very few patients. These findings suggest that, with their complementary mechanisms of action, empagliflozin added on to basal insulin may be a useful treatment option in patients on basal insulin who need additional glycemic control without weight gain.